Re-Discovering a Roman Wall Painting at Harvard: New Research on a Fragment from the Villa at Boscotrecase. (3rd July 2020) - Molacek, Elizabeth M.; Smith, Kate; Eremin, Katherine; Cooper, Lucy J.; Rayner, Georgina
ABSTRACT: This article presents historical and scientific analysis, as well as the conservation treatment of a newly rediscovered Roman wall painting fragment, now in the collection of the Harvard Art Museums. Although the piece has not previously been published, it was among a group of fragments removed from a Roman villa near Boscotrecase in southern Italy, an area that has been key to the study of Roman wall painting and other decoration. Technical imaging confirms the use of painting techniques consistent with other high-quality paintings in the area. Materials analysis revealed a palette consistent with published findings of Roman wall paintings, including abundant use of Egyptian blue and green earth. Of interest was the use of Egyptian blue as an optical brightener in select white passages. Despite the high quality of the painting, no cinnabar was present, and all red passages were achieved using hematite. Multiple different white minerals were identified including calcite, aragonite, and gypsum. The widespread presence of gypsum is unusual and may point to alteration.